Finding of fimbriocercus of Taenia sp. (Cestoda: Taeniidae) in the yellow-rumped leaf-eared mouse (Phyllotis xanthopygus) - Gomez-Puerta, Luis A. (2017)
Metacestodes were collected from the peritoneal cavity of the yellow-rumped leaf-eared mouse (Phyllotis xanthopygus) from the Marangani district in Cuzco, Peru. A total of 6 metacestodes were studied and identified as fimbriocercus of Taenia sp. The fimbriocercus had a slightly elongated and spherical body, with a mass of dense tissue and whitish milky color. Each fimbriocercus had an invaginated scolex which had 4 suckers and a rostellum armed with 22 to 25 pairs of hooks. This study shows that the mouse P. xanthopygus participates as an intermediate host for a Taenia species in the southern highlands of Peru.